2020
DOI: 10.1093/jpids/piaa040
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental Respiratory Syncytial Virus and Influenza Virus Antibody Transfer in Alaska Native and Seattle Mother–Infant Pairs

Abstract: Background Alaska Native (AN) infants are at risk for severe disease due to respiratory syncytial virus (RSV) and influenza. Maternal immunization protects young infants through transplacental antibody transfer. RSV- and influenza-specific transplacental antibody transfer in mother–infant pairs has not previously been evaluated in the AN population. Methods Serum samples collected during pregnancy and at birth from AN mother–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The mean log RSV Ab titre and the CMTR in Australian First Nations infants were equivalent to levels in Alaska Native infants. 17 The CMTR observed in our study was comparable to other highburden populations with similar socio-demographic risk factors 18 but there are many unique factors that are specifically linked to Fist Nations population which were not reflected in our study cohort. For example, as all the mother-infant pairs in this study were part of a vaccine trial whereby only pregnant women with uncomplicated pregnancies were recruited, all our infants were born at term and findings from our study do not represent the transfer efficiency of maternal RSV Ab in 14% of First Nations children who are born preterm (GA ≤36 weeks) 8 and are more likely to have CMTR of <1.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The mean log RSV Ab titre and the CMTR in Australian First Nations infants were equivalent to levels in Alaska Native infants. 17 The CMTR observed in our study was comparable to other highburden populations with similar socio-demographic risk factors 18 but there are many unique factors that are specifically linked to Fist Nations population which were not reflected in our study cohort. For example, as all the mother-infant pairs in this study were part of a vaccine trial whereby only pregnant women with uncomplicated pregnancies were recruited, all our infants were born at term and findings from our study do not represent the transfer efficiency of maternal RSV Ab in 14% of First Nations children who are born preterm (GA ≤36 weeks) 8 and are more likely to have CMTR of <1.…”
Section: Discussionsupporting
confidence: 61%
“…The mean log RSV Ab titre and the CMTR in Australian First Nations infants were equivalent to levels in Alaska Native infants. 17 Although we did not compare our results to non-Aboriginal mother-infant pairs, the study done in Alaska Native infants showed that levels of maternal RSV Ab level in Alaska Native infants was significantly lower than their comparator group who were predominantly white infants in United States (75 Alaska Native mother-infant pairs enrolled from Bethel, Alaska vs. 57 mother-infant pairs from Seattle). A similar trend could be observed in Australia and warrants exploration, based on the data from this study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Few published studies have evaluated this for RSV, but one study of 213 infants found that those born < 37 weeks (both preterm low birthweight and preterm adequate birthweight) had lower CMRs for RSV compared to term infants (both term-low birthweight and term-adequate birthweight) in The Gambia [53] . A more recent study assessing RSV CMR among 75 Alaska Native mother-infant pairs found that infants with CMR < 1.0 were more likely to be lower birth weight or preterm than infants with CMR > 1.0 [54] . Similar findings were noted in a recent study of pregnant women in Kenya [55] .…”
Section: Potential Inhibitors Of Transplacental Transfer Of Maternal ...mentioning
confidence: 99%
“…Maternally derived RSV antibodies are efficiently transferred to the foetus and have been shown to be inversely associated with acute lower respiratory tract RSV infection and disease severity [15,16]. Ensuring an abundance of high quantity, neutralizing antibodies through the first several months of life could substantially lessen the disease burden in new-borns [17]. Maternal immunization (MI), or immunization during pregnancy has been a common practice resulting in substantial global impact by providing protection against infectious disease for the mother, child, or both [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%